2021
DOI: 10.1093/jbcr/irab117
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Burn Outpatient Clinic Referrals to ABA Criteria in a Tertiary Center: Creating Unnecessary Referrals?

Abstract: Initial assessment and triage of burns is guided by the American Burn Association criteria for referral to a burn centre. These criteria are sensitive but not specific, and can potentially lead to over-triage and “unnecessary” clinic visits. We are a Level 1 trauma centre with burn subspecialty care, and due to the COVID-19 pandemic, referrals to our multidisciplinary outpatient burn clinic required triaging for virtual care appointments. In order to improve the triage process, we retrospectively reviewed our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…66 Looking forward, making outpatient referral criteria more specific may be beneficial to address this. 66 Although the previous study examined burn outcomes in the United States, multiple studies show how patients were impacted globally. In an article from an Italian hospital, designated as a "COVID-19 pediatric hub," the characteristics of the pediatric burn patients during the COVID-19 pandemic were described.…”
Section: Burn Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…66 Looking forward, making outpatient referral criteria more specific may be beneficial to address this. 66 Although the previous study examined burn outcomes in the United States, multiple studies show how patients were impacted globally. In an article from an Italian hospital, designated as a "COVID-19 pediatric hub," the characteristics of the pediatric burn patients during the COVID-19 pandemic were described.…”
Section: Burn Managementmentioning
confidence: 99%
“…This further highlights the requirement for urgent public health communication and injury prevention strategies to decrease these preventable occurrences. On top of that, a Canadian level 1 trauma center found that pediatric burns were being overtriaged and led to an increase in unnecessary appointments despite attempts to limit the number of outpatient clinic visits 66 . Looking forward, making outpatient referral criteria more specific may be beneficial to address this 66 …”
Section: Burn Managementmentioning
confidence: 99%